Passive markers as a low-cost method of enriching cultural visits on user’s demand - Koutsoudis, Anestis; Arnaoutoglou, Fotis; Pavlidis, George (Journal of Advanced Computer Science & Technology, 2014)
The idea of enriching a cultural heritage visitor’s experience by employing mobile devices such as smartphones and tablets is an active research domain. This is mainly due to the worldwide user penetration of such devices along with their continuous hardware performance enhancement. This work presents the experience and feedback gained by one year of operation of an experimental information system that aims in enhancing the experience of a visitor on his/her demand. The evaluated system is based on the use case-scenario where the a mobile device is used to capture and decode passive markers (such as QR-codes) that are located on facades of selected important buildings in the old town of Xanthi, Greece, in order to enrich the visitor’s experience through a broad context of historical and architectural information delivered over the Web. Keywords: On-demand information, Passive marker, QR-code, Smartphone, Visit enrichment.